Islamic manufacturing practice: current development and future prospects / Muhammad Hafiz Hamzah - Hamzah, Muhammad Hafiz (2010)
The aim of this research project is to study the relationship between Islamic Manufacturing Practice (IMP) standard and other quality standards available in Malaysia like Quality Management System (MS ISO 9001:2008), Food Safety according To Hazard Analysis and Critical Control Point (HACCP) System (MS 1480:2007), Halal Food (MS 1500:2004) and Good Manufacturing Practice (GMP) (MS 1514). Concepts of the IMP System are addressed, followed by a description of different management system and their interrelations. Subsequently, the current developments of IMP in Malaysia were studied by conducting a case study at a company which are adopting and practicing the IMP Standard. The investigation focused on the actual application of the IMP standard, and highlighted other standards that being practiced at the case study subject and how these standards harmonized into a complete system. A comparison study between the Quality Management Standards mentioned above against the present IMP standard is presented. From here the current IMP standard were benchmark against those standards and put forward a more comprehensive IMP standard and internationally recognized. Finally, a discussion on the development of a generic IMP standard is provided through an integration of these quality standards which consists of international recognized quality systems and ethical qualities that emphasised on Islamic Management Practice.